Do IFO indicators help explain revisions in German industrial production? - Jan P.A.M. Jacobs; Jan-Egbert Sturm (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper studies the information content of some Ifo indicators. In particular, we investigate whether two Ifo indicators, one on the current business situation, the other on current production development, provide information on revisions of German industrial production. A new feature of our analysis is the construction and use of a real-time dataset. We conclude that the Ifo indicators play a role in explaining revisions, but counterintuitively the business situation indicator performs better than the production indicator.
Keywords: C22; C53; C82; 330; Ifo business survey indicators; German industrial production; real-time analysis; data revision; Konjunkturindikator; Industrielle Produktion; Zeitreihenanalyse; Statistischer Fehler; Schätzung; Deutschland